Ways to improve food safety efficiency through digital technologies - Saidova Gulnoza Tulkunovna, (THE INNOVATION ECONOMY, 2026)
The article is devoted to strengthening food security in Uzbekistan through the development of digital technologies in the food production and processing chain. In particular, an assessment of the factors affecting food security in the context of sustainable development of industry and agriculture is given. Within the framework of the concepts of "Agriculture 4.0" and "Industry 4.0", issues of digitalization of the food production and processing chain, ensuring food security and strengthening food security by improving the organizational and economic mechanisms of "smart agriculture" and "smart industry" are considered